Void growth mitigation in high heating rate Out-of-Autoclave processing of composites - Rengaraj, Kishen (2016)
Increased pressure on the transport industry to reduce greenhouse gas emissions has hastened the adoption of high performance composites, particularly in the aerospace industry where the value of weight saving is very high. However, the current method of choice for manufacturing high performance composites (autoclave processing) is not cost effective for processing large (greater than 5m2) structural composite components. Developments in Out-of-Autoclave (OoA) prepreg systems have facilitated the use of vacuum only consolidation pressure to process laminates with autoclave level mechanical properties. However, owing to the low consolidation pressure, the process is heavily dependent on de-bulk quality and low cure temperatures; leading to reduced margin for error as well as long cycle times. In parallel, developments in high heating rate OoA processes have been shown to enable short cure cycle times and autoclave-level mechanical properties; albeit with a high tendency towards porosity. To date, studies on high heating rate OoA processing have been limited and the processes are not well understood.